VECAP ensures sustainable management of brominated flame retardants in Europe. Issue 12 (December 2018) - Unknown
Abstract : The European Flame Retardant Association (EFRA) has released its latest annual VECAP progress report covering the year 2017. VECAP, the Voluntary Emissions Control Action Programme, is a product stewardship initiative that aims to reduce potential emissions of brominated flame retardants (BFRs) during production and end use by promoting environmental best practices.